Indonesian honey bioactivity profile linking composition to antioxidant and antibacterial potency - ACHMAD GUS FAHMI; AKHMAD ENDANG ZAINAL HASAN; NOVRIYANDI HANIF; YAYA RUKAYADI; KHOZIRAH SHAARI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Fahmi AG, Hasan AEZ, Hanif N, Rukayadi Y, Shaari K. 2025. Indonesian honey bioactivity profile linking composition to antioxidant and antibacterial potency. Biodiversitas 26: 4991-5002. Indonesian honey, sourced from diverse tropical flora, is valued for its antimicrobial and antioxidant properties, yet comparative multi-parameter studies are limited. This study evaluates five Indonesian honey types (Akasia/Acacia carpa honey, Rambutan/Nephelium lappaceum honey, Randu/Ceiba pentandra honey, Flores honey, and Kelulut honey) for physicochemical traits, bioactive compounds, antioxidant capacity, and antibacterial activity against Escherichia coli and Salmonella Typhi. Physicochemical analysis determined pH, moisture, ash, and color. Total phenolic content (TPC) and total flavonoid content (TFC) were measured spectrophotometrically. Bioactives were identified via LC-MS. Antioxidant activity was assessed by DPPH radical scavenging and antibacterial efficacy was tested using disk diffusion. Data were analyzed using ANOVA and principal component analysis (PCA). All samples adhered Codex and SNI (RSNI3 8664:2024) quality standards. Flores honey had the highest TPC (4526.12 mg GAE/100 g) and TFC (3810.96 QE/100 g), yielding superior antioxidant activity (IC??: 2.11±0.03 mg/mL). Kelulut honey showed the strongest antibacterial effect (inhibition zone: 13.50 mm against E. coli and 9.42 mm against Salmonella Typhi), linked to amino acids (L-proline, leucine) and phenolic acids (caffeic, quercetin). PCA revealed distinct clustering by bioactive profile: phenolic/flavonoid-rich honeys (e.g., Flores honey) aligned with antioxidant potency, while amino acid-rich honeys (e.g., Kelulut honey) correlated with antibacterial activity. Indonesian honey exhibits diverse and potent bioactivities, surpassing or matching Southeast Asian and Manuka honeys in key metrics. Flores honey represents a promising dietary antioxidant source, while Kelulut honey shows potential for antimicrobial applications such as topical formulations. Future work should isolate and characterize specific bioactives to support functional food and therapeutic development.